A Five-Pillar Model of the Ideal Islamic Education Teacher: Synthesizing Al-Ghazali and Ibn Khaldun - Maghfiratun Mardiyah; Maulana Aqso; Muhammad Ilham Sofwani; Nabila Shinta; Dian Namora (Al-Mudarris, 2025)
This study reconstructs the concept of the ideal teacher in Islamic education through a comparative analysis of the educational philosophies of Al-Ghazali and Ibn Khaldun and examines their relevance to contemporary Islamic Religious Education (IRE). Employing a qualitative library research design with comparative analysis, qualitative content analysis, thematic synthesis, and classical text hermeneutics, the study explores the similarities, differences, and complementary perspectives of both scholars to formulate a comprehensive framework for Islamic teacher professionalism. The findings indicate that Al-Ghazali emphasizes the ethical-spiritual dimension of teacher professionalism by positioning teachers as murabbi ruhani who cultivate students' faith, morality, and closeness to Allah. In contrast, Ibn Khaldun highlights pedagogical competence, learner-centered instruction, developmental psychology, and contextual learning as the foundation of effective teaching. Integrating these complementary perspectives, this study proposes the Five-Pillar Model of the Ideal Islamic Education Teacher, consisting of spiritual integrity (taqwa), ethical exemplarity (uswah hasanah), academic competence ('alim), pedagogical competence (mudarris), and contemporary adaptability. The principal theoretical contribution of this study is the development of the Five-Pillar Model as an integrated conceptual framework that reconstructs the complementary educational philosophies of Al-Ghazali and Ibn Khaldun to strengthen Islamic teacher professionalism in the era of digital transformation and Society 5.0. The model provides a theoretical foundation and practical guidance for teacher education, curriculum development, competency standards, and continuous professional development in contemporary Islamic education.